Współczesna filozofia prawa wobec fanatyzmu religijnego - Szymaniec, Piotr (Przegla̜d religioznawczy, 2015)
The paper presents three strategies that contemporary philosophy of law has developed to respond to emerging challenges currently associated with the religious fanaticism. The first of them - represented by Günther Jakobs - relies on preventive measures against the "enemies" of the constitutional order, for example against the religiously motivated terrorists. However, the concept of Feindstrafrecht by G. Jakobs is burdened with the arbitrariness in defining the category of "enemies" and undermines the privacy and the principle of ideological neutrality of the state. Ronald Dworkin is a representative of the second strategy. In his last book, Religion without God, Dworkin wants to eliminate the extreme attitudes by reducing the religious freedom to the general right to ethical independence. His approach, however, completely ignores the collective aspect of the religious freedom. Jürgen Habermas proposed a different strategy. His concept, which is the most interesting of the aforementioned in terms of application, on the one hand shows the conditions for the inclusion of religious positions in the area of democratic, rational discourse, and on the other hand it excludes from area of this freedom the religious fanaticisms which do not accept the constitutional consensus of the democratic state. In the author’s opinion, the reflection on the conditions of the limitations on the freedom of religion, which are necessary nowadays, should be complemented by John Stuart Mill’s classical test of harm principle as well as by the use of Amartya Sen’s capabilities approach. These concepts allow us to define in a better manner the situations in which, on the one hand, the actions based on religious beliefs lead - or may lead - to harm of other people and, on the other hand, the religious communities in an unauthorized way restrict the freedom of their own members. Furthermore, the harm principle gives also the opportunity to take some tough decisions in the cases concerning religiously motivated actions of private individuals, e.g. in situations concerning the consent to medical procedures with respect to family members who are not able to make a valid decision.